PENGARUH HARI LIBUR NASIONAL TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Chandra Siregar, Viky Hari; Hindasah, Lela (Journal of Accounting and Investment, 2010)
This research conducted to know (1) what 1 day before and after National holiday have an effect on to return share compared to other commerce day. (2) What national holiday which carried over by a weekend have an effect on to return share compared to holiday remain to on which in fact. (3) To test the effect of National holiday to return share that happened before and after National holiday. This research use data sample an LQ45 index 2004-2008, that is to avoid the inactive share. Data obtained from corner of Bursa Efek Indonesia of UNDIP Semarang. Statistic test used in this research is Box Jenkins or referred as ARIMA (Autoregressive Integrated Moving Average). Result of this research indicate that (1) There are not significance effectÂ  between 1 day before and after National national to return share compared to other commerce day. (2) There are not significance effect of National holiday which is carried over by weekend to return share compared to ordinary holiday. (3) There are significance effect between Thursday before holiday of Friday national to return share.